(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Diabetic nephropathy remains a significant complication of diabetes mellitus, characterized by kidney damage due to prolonged high blood sugar levels. Glycated hemoglobin (HbA1c) is a crucial indicator of long-term glucose control in diabetic patients. Recent studies have suggested a potential association between blood klotho levels, a protein with renal protective properties, and glycemic status in diabetic nephropathy. This study aims to explore the relationship between blood klotho levels and glycated hemoglobin in diabetic nephropathy patients.